A Comparative Study of Field Emission From Pristine, Ion‐Treated and Tungsten Nanoparticle‐Decorated p‐Type Silicon Tips. Issue 9 (14th March 2019) - Kleshch, Victor I.; Serbun, Pavel; Lützenkirchen‐Hecht, Dirk; Orekhov, Anton S.; Ivanov, Victor E.; Prommesberger, Christian; Langer, Christoph; Schreiner, Rupert; Obraztsov, Alexander N.
Abstract : The field electron emission characteristics of individual tips of a silicon field emitter array are analyzed. The array of conical‐shaped tips is fabricated on a p‐type silicon wafer by using reactive ion etching and sharpening oxidation. The tips are decorated with single tungsten nanoparticles at their apexes. Furthermore, the focused ion beam is also used to increase surface conductivity of some of the tips. Comparative measurements of field emission are performed by using the scanning anode probe field emission microscopy technique. All types of tips demonstrated emission activation consisting of a sudden current increase at a certain value of the applied voltage. Compared to the pristine tips, a noticeable reduction of the saturation effect in the current–voltage characteristics and a smaller light sensitivity for the decorated tips is found. For ion‐treated tips, saturation effects and light sensitivity are completely suppressed. Scanning electron microscopy observations reveal the formation of single nanoscale protrusions extending from the metal particles and from the apexes of bare ion‐treated tips after exposure under strong electric fields during the field emission measurements. The influence of protrusions growth on characteristics of silicon field emitter arrays is discussed. Abstract : The field electron emission characteristics of individual silicon tips are analyzed. Noticeable reduction of the saturation effect in the current–voltage characteristics for the nanoparticle‐decorated tips is found. For ion‐treated tips the saturation effects are completely suppressed. All types of tips demonstrated emission activation which is attributed to the formation of single nanoscale protrusion extending from the emitter's apex.